Efektifitas Media Tebak Gambar dalam Menghafal Mufrodat di Kelas VII N MTS Assunniyyah - Ghofur, M. Abdul; Islamiyyah, Dina Ulya (UAS PRESS, 2023)
The success of the learning process cannot be separated from the role of the media, because educational tools and media are an integral part of the educational process in schools. One of the methods used by educators to make it easier for students to memorize mufrodat is to use picture guessing media. The purpose of this study was to find out the application and effectiveness of picture guessing media in memorizing Arabic mufrodat and knowing the results of memorizing using picture guessing media. The research method used is a qualitative descriptive method focusing on the effectiveness of picture guessing media in memorizing mufrodat. The results of the research on picture guessing media make it easier for students to memorize Arabic mufrodat where the more students memorize mufrodat, the easier it is for students to understand Arabic writings. In addition, it is the teacher's effort to improve mufrodat memorization. With the guessing picture media, students are more enthusiastic about memorizing Arabic mufrodat.